Optimizing fisheries potential through increasing entrepreneurial literacy and market access for the Ohoi Revav community - Ikram Mubarak Djodding; Nurhayati Bugis; Demianus Toatubun (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines efforts to optimize the fisheries potential of Ohoi Revav through the enhancement of entrepreneurial literacy and improved market access among local students. Recognizing the strategic role of fisheries in supporting local economic development, the study explores how entrepreneurial knowledge and business motivation can encourage greater participation in fisheries-based economic activities. Employing a qualitative descriptive approach, data were collected through participatory observation and in-depth interviews to gain a comprehensive understanding of the relationship between entrepreneurial literacy, market accessibility, and community economic empowerment. The findings indicate that increased entrepreneurial literacy has strengthened students’ awareness of the economic value of fisheries resources and encouraged the adoption of innovative business practices, including the utilization of digital platforms for marketing and promotion. Improved market access has also facilitated stronger collaboration between students and local fishermen, contributing to more sustainable economic activities and positive socio-economic outcomes within the community. These findings highlight the importance of entrepreneurship education and market connectivity in fostering local economic development and strengthening fisheries-based enterprises. Nevertheless, the study is limited by its relatively small number of participants and short observation period. Future research is recommended to involve broader community groups and further explore digital marketing and entrepreneurship strategies to enhance the long-term sustainability and competitiveness of local fisheries businesses. Keywords: Fisheries Potential; Entrepreneurial Literacy; Market Access; Ohoi Revav; Student Empowerment